Internet addiction and its association with depression, anxiety, and stress symptoms among allied health students in Malaysia (Faculty of Medicine Universitas Indonesia, 2022)
BACKGROUND Internet addiction (IA) is prone to be experienced by students and has become a major health concern. However, data on IA among allied health students are limited. This study aimed to describe the prevalence of IA and the association between mental health problems and IA among allied health students in Malaysia. METHODS A cross-sectional study was conducted from July to December 2021 in three government-funded allied health training institutes in Malaysia. A total of 265 allied health students undertaking a diploma in nursing, medical assistant training, physiotherapy, occupational therapy, and diagnostic imaging were recruited using stratified random sampling. The Malay version of the IA test was used to measure IA, while depression, anxiety and stress scale-21 items were used to assess their mental health problems. A general linear model was used to analyze the association between IA scores and mental health problems. RESULTS The prevalence of IA among allied health students was more than 80%, with 16.2% and 2.3% of them reporting moderate and severe IA, respectively. Higher depression (p<0.001), anxiety (p<0.001), and stress scores (p = 0.002) were associated with higher IA scores. CONCLUSIONS There were significant associations between mental health problems and IA scores among allied health students. Future studies with rigorous scientific methods are necessary to explore mental health effects on IA. Early intervention is also needed to prevent mental health problems among allied health students to overcome the problem of IA.